The Effect of Social Media Content on Buying Decision of HijUp.com - Tyas, Anggorowati; Hutagaol, Olivia (Journal of Communication and Public Relations, 2021)
Social media is a channel to socialize with each other via online so that people can interact with each other without limited space and time. A variety of business sees many opportunities in the online media that can be used as a place to sell goods and services. Social media appears one of them is Facebook, Instagram, Twitter, YouTube and other social media. Hijup, a muslim fashion e-commerce, utilizes social media such as Instagram and Facebook to perform marketing strategies for its products. This study aims to determine the effect of social media content facebook and instagram on buying decision Hijup.com, to know the direction and influence of social media content facebook Hijup who play a role in buying decision at Hijup.com. The main theory used for this research is Elaboration Likelihood Model (ELM) to explain persuasion that sees every individual becomes very rational when evaluating persuasion messages, messages received differently for each individual then the impact will also be different. This research is using quantitative methodology with positivistic paradigm and explanatory of causality approach by using survei on 100 respondents. Hypothesis test results stated that there is a positive influence between social media content facebook and social media content Instagram simultaneously to the decision of purchase Hijup. There is a positive direction of influence on facebook social media content on purchasing decisions.